Avaliação do desempenho e do conforto térmico de uma edificação ventilada naturalmente segundo as normas brasileiras de desempenho térmico e a ASHRAE 55 - Leila Guedes Alvim (2015)
The growing concern about the rational use of natural resources and energy efficiency of buildings has highlighted the importance of constructions performance. In 2005, the first Brazilian standard on thermal performance for low-income housing was published, NBR 15.220. After that, in 2013, another building performance standard that applies to all residential buildings was published, NBR 15.575. The present study aims to evaluate the thermal performance of a house located in Belo Horizonte according to the two Brazilian performance standards mentioned above. In the NBR 15.220 evaluation, this study checks the fulfillment of the constructive guidelines for the bioclimatic zone 3 (ZB3), the zone indicated for this city in the Brazilian bioclimatic zoning, and also for the bioclimatic zone 4 (ZB4), zone indicated by Pereira and Assis (2005) as the most appropriate for the city. Thermal comfort assessments are performed, for the actual building with its original features as well as for modified versions of the building that meet with the constructive guidelines of the two thermal performance standards in the prescriptive method. The results are compared with a thermal comfort assessment according to the American ASHRAE Standard 55, in the adaptive model. The results show that the percentage of comfort hours obtained in the buildings that comply with the design guidelines of the two performance standards has increased when compared to the building with the original features, in all cases. An inconsistency was found in the Brazilian bioclimatic zoning during the NBR 15.220 analysis, as the compliance with the constructive guidelines for ZB4 provided a building with a better thermal performance than one that complies with the constructive guidelines for ZB3. It was also found that NBR 15.575 does not provide all the data needed to run a computer simulation, what makes the process more difficult and subjective. The simulation procedure of the NBR 15.575 standard does not allow an annual assessment nor consider the actual use of the building, like the presence of internal loads and natural ventilation strategies, undermining an effective evaluation.